Nourishing waters, comforting sky thirty-five years at a sandhills oasis - Jones, Stephen R., 1947- (Book collections on Project MUSE., 2022)
"Stephen R. Jones's collection of essays explores the natural and cultural history of the Sandhills, giving attention especially to the engaging and fragile beauty of the public-private ecosystems that surround and compose the Crescent Lake National Wildlife Refuge in western Nebraska"--